Towards a broader understanding of selection of students to train as health care professionals - Pillay, D.; Ross, A. (South African Journal of Higher Education, 2016)
Introduction: Institutes of Higher Learning (IHL) must train healthcare professionals (HCPs) able to meet priority needs of the population and address health system deficiencies. Concerns about the mismatch between outcome and policy have led many IHL to review their curriculum content. We argue for a broadening of selection criteria when choosing students to train as HCPs. Methods: A narrative inquiry drawing on life-history interviews and art-based methods was used to generate and collect data on lived lives as told and experienced by six rural-origin HCPs. Results: Analysis of two narrative vignettes framed as dilemmatic spaces show how personal beliefs and practices inform perspectives that HCPs adopted in their learning and development at IHL, and the transformational practices they enacted. Discussion: How competing forces were negotiated and positions were taken in committing to become HCPs with the capacity to lead transformation is described. Introducing and using dilemmatic spaces analytically enabled deeper understanding of beliefs and priorities that are important to consider alongside academic potential.